Making sense of the sharing economy: a business model innovation perspective. Issue 8 (2nd August 2020) - Sanasi, Silvia; Ghezzi, Antonio; Cavallo, Angelo; Rangone, Andrea
ABSTRACT: The emergence of a sharing revolution is leading to a new societal system of collaboration enabled by digital technologies. Although sharing-based initiatives are re-shaping established organisational practices and innovating traditional business models (BMs), existing research fails in grasping the phenomenon's multiple facets. This study aims at making sense of the Sharing Economy (SE) by shedding light on how startups embed the social trend of sharing and leverage digital technologies to develop innovative BMs. We attempt to solve the current theory-practice misalignment by proposing an original framework, definition, and classification of SE startups. The study presents a cluster analysis on 196 SE startups. We argue that SE startups group into five clusters: (i) pseudo-sharing; (ii) gig economy; (iii) crowd-based economy; (iv) pooling economy; and (v) P2P rental. This study contributes to positioning the SE from both a conceptual and an empirical perspective, interpreting the SE phenomenon from the theoretical lenses of BM Innovation, and classifying it through the unit of analysis of startups, intended as empirical vehicles and manifestation of the phenomenon.